2012
DOI: 10.1002/jrs.4073
|View full text |Cite
|
Sign up to set email alerts
|

Automated identification of components in a chemical mixture utilizing multi‐wavelength resonant‐Raman spectroscopy and a Pearson correlation algorithm

Abstract: In complex environments, the ability to identify the constituent chemicals within a mixture is extremely important. By utilizing a Pearson correlation algorithm to compare sets of multi-wavelength resonance-Raman signatures, we demonstrate the automated identification of chemicals within a mixture. Applying a linear mixture model, we are also able to estimate the fractional volumetric abundances contained therein. The multi-wavelength resonance-Raman signature used for identification is obtained by illuminatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…We have previously demonstrated the use of two-dimensional resonance Raman spectroscopy in identifying constituent components of chemical mixtures with the use of Pearson correlation coefficient-based algorithms. 14 We employed a similar technique here to distinguish between bacterial species. The 2D Raman signatures were grouped into 12 classes based on growth condition, three classes for each of the four species, and assembled into a signature library.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated the use of two-dimensional resonance Raman spectroscopy in identifying constituent components of chemical mixtures with the use of Pearson correlation coefficient-based algorithms. 14 We employed a similar technique here to distinguish between bacterial species. The 2D Raman signatures were grouped into 12 classes based on growth condition, three classes for each of the four species, and assembled into a signature library.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple-wavelength resonance Raman spectroscopy has been demonstrated to offer significant advantages over conventional Raman spectroscopy in distinguishing between different types of bacteria and chemicals, especially when they are present in complex mixtures. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…Lau and co‐workers developed a Bayesian Whittaker–Henderson smoother for general‐purpose and sample‐based spectral baseline estimation and peak extraction . Lunsford and co‐workers described a Pearson correlation algorithm for the automated identification of components in a chemical mixture utilizing multi‐wavelength resonant‐Raman spectroscopy . Widjaja and Garland presented a detailed spectroscopic analysis of complex multicomponent materials using a combination of Raman mapping with band‐target entropy minimization …”
Section: Special Raman Techniques and Methodsmentioning
confidence: 99%
“…This type of additional information has already been shown to aid in the detection of materials in complex environments. 14–16 The shifted correlations illustrate the potential of swept wavelength techniques by showing the isolated effect of variations in Raman band intensity at different wavelengths. Measurements in the visible range suggested that the identification mechanisms are primarily evident in the UV, or resonance Raman, region.…”
Section: Resultsmentioning
confidence: 94%
“…A swept-wavelength spectrum provides a linearly independent set of Raman spectra, further discussed in Appendix 1, which enables improved signal processing by measuring not only the wavenumber of Raman peaks but also the shape of the peaks as a function of wavelength. This has previously been shown to increases the accuracy of sample identification in complex mixtures with overlapping Raman peaks, 14 correctly identifying each component in a set of 31 unique mixtures, while single wavelength measurements were insufficient in up to 25% of the cases. Increased specificity has also been demonstrated 15 by calculating the ratio of Raman band intensities with as few as two wavelengths.…”
Section: Introductionmentioning
confidence: 99%